Research on the Inheritance and Evolution of Tai Chi Routines Propelled by Digital Innovation: Mechanisms, Practices, and Prospects - Lu, ding; Wang, Keqiao (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details